Production of Polyurethane from Liquefied Kenaf (Hibiscus Cannabinus L.) Core for Wood Laminating Adhesive - Mohd Fadzil, Juhaida (2009)
Kenaf is one of the several fibre crops that have been identified as potential source of natural long fibres. The only economical way to use this plant is to extract the long fibres from the bast and used it for fibre reinforced plastic composites to replace glass fibre which are known to be environmental unfriendly. Once the basts have been separated from the stem, the inner, soft and woody section – also known as kenaf core (KC) – can be used for other applications such as biochemicals, due to high amount of holocellulose content and low lignin content. Some of the chemicals that can be derived from KC include polyols, carboxymethyl cellulose, and cellulose esters. This study was carried out to produce polyurethane (PU) adhesive from liquefied kenaf core (LKC) polyols by reacting it with toluene-2,4-diisocyanate TDI). The liquefaction of KC powder was conducted in the presence of polyethylene glycol (PEG) 1000 and sulfuric acid as a catalyst. The optimum reaction condition (i.e., temperature and time) for producing polyol from KC was determined based on the percentage of reaction residues. Lower reaction residues indicate more KC powder being liquefied in the solvent system. The extent of liquefaction in various mixtures of PEG 1000 and glycerol was also analysed. It was found that the percent residue of KC decrease with an increase of liquefaction temperature up to 180°C and time of up to 90 minutes. When the liquefaction reaction was maintained for 120 minutes, the amount of residue, however, increased quite significantly. This increment can be associated with the formation of recondensation of the LKC components as by-product of the reaction. The percent residue of unliquefied KC was found to be relatively lower when the glycerol:PEG ratio was increased from 1:17 to 3:15 suggesting a more complete liquefaction of KC has taken place. At glycerol:PEG ratio of 5:13, however, the amount of residue was slightly increased suggesting recondensation of the lignin during liquefaction process. Hence, it is important to liquefy the KC before the recondensation point was reached. The PU adhesive was successfully synthesized using polyols from LKC. The LKC polyurethane (LKCPU) adhesive has a molecular weight (MW) of 2,666, viscosity of 5,370 cps, and solids content of 86.9%. In gluing study, the shear strength of the bonded rubberwood with LKCPU adhesive shows an average of 2.9 MPa. No wood failure was observed on the sheared specimens, showing that the adhesive strength is weaker than wood. The thick LKCPU mixture was relatively difficult to be spreaded onto the wood surface so much so reduced the penetration into the wood. Thus, coupled with the uneven pressure during clamping caused the adhesive to fail upon loading. The formation of air bubbles through liberation of carbon dioxide during curing process resulted in weak cohesive strength of the adhesive as can obviously seen on the sheared specimens. Nonetheless, based on the properties of the LKCPU produced in this work, it has great potential as wood laminating adhesive particularly for edge-gluing